PLASTINATED MODELS AS TEACHING AIDS IN THE EDUCATIONAL INSTITUTIONS - Menaka, R (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The anatomical teaching aids preservation and preparation is a challenging artist work in the current scenario. Alternative teaching tools to be innovatively modified as per our indigenous technique to preserve the cadavers for longer durations. The equine limbs were used for plastination procedure and further treated with colorless varnish paint to pleasant look to handle it in laboratory conditions. The plastinate models were replaced with wet dripping formalin fumes in anatomical dissection hall. Simultaneously, the anatomical descriptions also well understand by its topographical position of adjacent structures due to its transparency of specimen. The plastination technique invites curiosity about education and research in the subject of veterinary anatomy, pathology and surgery. The plastinated models well recognized as good teaching tools in the anatomical laboratory as well as biological museum all over the world.